2021
DOI: 10.1186/s12885-020-07778-1
|View full text |Cite
|
Sign up to set email alerts
|

Recent incidence trend of elderly patients with glioblastoma in the United States, 2000–2017

Abstract: Background The incidence of glioblastoma increases significantly with age. With the growing and aging population, there is a lack of comprehensive analysis of recent glioblastoma incidence trend in the United States. This study aims to provide in-depth description of the patterns of incidence trends and to examine the age-period-cohort effects to the trends of glioblastoma specific to elderly patients. Methods The incidence rates were age-adjusted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 39 publications
2
34
0
Order By: Relevance
“…A study in the United States showed that the average incidence rises with age. If we consider the whole population of the United States, the incidence stands at around 3.2 per 100,000 people [4,13], which is in accord with the worldwide average incidence that ranges from 0.59 to 5 per 100,000 people [14]. If we age adjust occurrences of glioblastoma, we see that the incidence rate rises to 15.47 per 100,000 people in age group ranging from 75 to 79 years old [13].…”
Section: The Genetic Component Of Glioblastomasupporting
confidence: 69%
See 1 more Smart Citation
“…A study in the United States showed that the average incidence rises with age. If we consider the whole population of the United States, the incidence stands at around 3.2 per 100,000 people [4,13], which is in accord with the worldwide average incidence that ranges from 0.59 to 5 per 100,000 people [14]. If we age adjust occurrences of glioblastoma, we see that the incidence rate rises to 15.47 per 100,000 people in age group ranging from 75 to 79 years old [13].…”
Section: The Genetic Component Of Glioblastomasupporting
confidence: 69%
“…If we consider the whole population of the United States, the incidence stands at around 3.2 per 100,000 people [4,13], which is in accord with the worldwide average incidence that ranges from 0.59 to 5 per 100,000 people [14]. If we age adjust occurrences of glioblastoma, we see that the incidence rate rises to 15.47 per 100,000 people in age group ranging from 75 to 79 years old [13]. The same thing was pointed out when Walker et al looked at the Canadian population between the years 2009 and 2013.…”
Section: The Genetic Component Of Glioblastomamentioning
confidence: 99%
“…However, even with timely and effective treatment, only 25 and 5% of patients can survive for more than 1 and 5 years, respectively, and the average survival time is only 12–18 months ( 6 , 7 ). Even worse, with the growth of aging population, incidence of GBM is increasing, leading to a serious threat to public health ( 8 ). Therefore, improving of GBM treatment is of great importance.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of GBM increases tremendously with age peaking between ages of 65 to 84 [7]. The overall incidence of GBM in the elderly is 13.16 per 100,000 persons [11]. Patients with GBM often have a poor prognosis with a median survival rate of 2 years despite therapeutic advances [11].…”
Section: Introductionmentioning
confidence: 99%
“…The overall incidence of GBM in the elderly is 13.16 per 100,000 persons [11]. Patients with GBM often have a poor prognosis with a median survival rate of 2 years despite therapeutic advances [11]. Also, anaplastic astrocytoma (AA) is a diffusely infiltrating malignant, astrocytic primary brain tumor [12].…”
Section: Introductionmentioning
confidence: 99%